GE_GERICHTE P/2358/2018 vom 27. September 2021 - GE Cour de justice (2021)
VIOL;CONTRAINTE SEXUELLE;FIXATION DE LA PEINE;CONCOURS D'INFRACTIONS;PEINE PRIVATIVE DE LIBERTÉ;IMPUTATION;EXPULSION(DROIT PÉNAL);TORT MORAL;DOMMAGE;INDEMNITÉ;DÉFENSE D'OFFICE | CP.190.al1; CP.189.al1; CP.47; CP.49.al1; CP.51; CP.66a.al1.leth; CO.49.al1; CO.41; CPP.433; CPP.135